2022
DOI: 10.1038/s41467-022-31201-x
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune responses against the fungal pathogen Candida auris

Abstract: Candida auris is a multidrug-resistant human fungal pathogen responsible for nosocomial outbreaks worldwide. Although considerable progress has increased our understanding of the biological and clinical aspects of C. auris, its interaction with the host immune system is only now beginning to be investigated in-depth. Here, we compare the innate immune responses induced by C. auris BJCA001 and Candida albicans SC5314 in vitro and in vivo. Our results indicate that C. auris BJCA001 appears to be less immunoinfla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 69 publications
9
59
0
3
Order By: Relevance
“…5 ). The same trend was observed in fungal infections, where Candida albicans appeared to be less immunoinflammatory and caused more cell death than Candida auris ( 28 ). When comparing the NETosis ability of different STs, we discovered that ST59 and ST398 promoted NETs formation and showed higher NADPH oxidase activity than ST239-MRSA and ST5-MRSA ( Fig.…”
Section: Discussionsupporting
confidence: 55%
“…5 ). The same trend was observed in fungal infections, where Candida albicans appeared to be less immunoinflammatory and caused more cell death than Candida auris ( 28 ). When comparing the NETosis ability of different STs, we discovered that ST59 and ST398 promoted NETs formation and showed higher NADPH oxidase activity than ST239-MRSA and ST5-MRSA ( Fig.…”
Section: Discussionsupporting
confidence: 55%
“…In vivo and in vitro studies carried out with the C. auris clinical isolate BJCA001 demonstrated that once the infection with the fungus is carried out in immunocompetent C57BL/6 female mice, the yeasts can remain in the host and evade the mechanisms of defense [ 66 ]. When the fungal load in infected organs was analyzed, increased tissue colonization was observed; however, no morphological changes, such as pseudohyphae or mycelium, were documented [ 66 ]. Although there was an increase in colonization, the inflammation and tissue damage suffered by the mice proved to be less severe than the infection caused by C. albicans [ 66 ].…”
Section: Pathogen–host Interaction In Different Nac Speciesmentioning
confidence: 99%
“…When the fungal load in infected organs was analyzed, increased tissue colonization was observed; however, no morphological changes, such as pseudohyphae or mycelium, were documented [ 66 ]. Although there was an increase in colonization, the inflammation and tissue damage suffered by the mice proved to be less severe than the infection caused by C. albicans [ 66 ]. In line with these observations, interactions with bone-marrow-derived murine macrophages showed a significant increment in the levels of IL-1β, IL-6, TNF-α, CXCL1, and CXCL2 when interacting with C. albicans but not when the experiments were performed with C. auris , suggesting that the latter is a lesser potent inducer of the MAPK signaling pathway [ 66 ].…”
Section: Pathogen–host Interaction In Different Nac Speciesmentioning
confidence: 99%
“…Chlorine-containing disinfectants and 2% chlorhexidine are currently used in clinical practice for environmental decontamination and skin decolonization, respectively 19 . Moreover, recent studies showed that C. auris may behave differently as other Candida species to induce innate immune responses 20 , 21 , 22 . C. auris tends to significantly reduce the innate immunoinflammatory response than C. albicans due to the thicker mannan layer of the cell wall 21 , facilitating its colonizations and infections in hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies showed that C. auris may behave differently as other Candida species to induce innate immune responses 20 , 21 , 22 . C. auris tends to significantly reduce the innate immunoinflammatory response than C. albicans due to the thicker mannan layer of the cell wall 21 , facilitating its colonizations and infections in hosts.…”
Section: Introductionmentioning
confidence: 99%